Assailing poverty and patriarchy, how does small money fare? - Khan, Monirul I.; Chowdhury, Mushtaque; Bhuiya, Abbas; Rana, Masud (BRAC, 2019)
This report is based on the findings of the case tracking study of 35 BRAC borrowers from Madab RDP over a period of one year Tracking began in July, 1996, and in all cases more than three months had elapsed before tracking began. The issues examined in this study are: background of the borrowers, use of loan, participation of the women in the use of loan, economic return on investment, borrowing from other sources, mobility of the borrowers or the decision making by the borrowers in their households related to the loan from BRAC. Findings revealed varied importance of credit for the BRAC borrowers. BRAC loans were a substantial support for the poor in terms of emergency funds and capital for multifarious investment. Despite access to loans from BRAC, they still borrowed from the moneylenders under compelling situations. It further found that the dominance of patriarchy was difficult to break because of its deep root in the society. Though observance of purdah varied, it was never absent and as such restricted the movement of women to a great extent. Patriarchal division of labour ensured that women remain confined mostly within household. The study concluded that these deep-rooted cultural factors were responsible for the perpetuation of women's subordination and micro-credit could not change it significantly.